1998
DOI: 10.1007/s007920050047
|View full text |Cite
|
Sign up to set email alerts
|

Purification of a ccb -type quinol oxidase specifically induced in a deep-sea barophilic bacterium, Shewanella sp. strain DB-172F

Abstract: We investigated for the first time the respiratory chain system of a deep-sea barophilic bacterium, Shewanella sp. strain DB-172F. A membrane-bound ccb-type quinol oxidase, from cells grown at 60 MPa pressure, was purified to an electrophoretically homogeneous state. The purified enzyme complex consisted of four kinds of subunits with molecular masses of 98, 66, 18.5, and 15kDa, and it contained 0.96 mol of protoheme and 1.95mol of covalently bound heme c per mol of enzyme. Only protoheme in the enzyme reacted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…Many y To whom correspondence should be addressed. Fax: +81-3-5317-9433; E-mail: htamegai@chs.nihon-u.ac.jp studies have been carried out on the respiratory system of S. violacea and on related strains for comparison, [19][20][21][22] but it remains unknown whether this phenomenon observed in S. violacea is universal to piezophiles.…”
Section: )mentioning
confidence: 99%
“…Many y To whom correspondence should be addressed. Fax: +81-3-5317-9433; E-mail: htamegai@chs.nihon-u.ac.jp studies have been carried out on the respiratory system of S. violacea and on related strains for comparison, [19][20][21][22] but it remains unknown whether this phenomenon observed in S. violacea is universal to piezophiles.…”
Section: )mentioning
confidence: 99%
“…These findings suggested that the expression of the respiratory system may be regulated by hydrostatic pressure, and this regulation may play some role in adaptation to high hydrostatic pressure. Indeed, expression of cytochromes is regulated by pressure in S. benthica DB172F (27,28) and S. violacea DSS12 (29).…”
mentioning
confidence: 99%
“…strain DB-172F was investigated by Qureshi et al, 1998. A membrane-bound ccb-type quinol oxidase was obtained from cells grown in a pressurized vessel.…”
Section: Oxidasementioning
confidence: 99%